Resilience and related factors in alcohol use disorder: the role of trauma, impulsivity, aggression, and temperament - Utkan, Naile Özge; Şenormancı, Güliz; Turan, Çetin; Metin, Salih; Şenormancı, Ömer (Frontiers in Psychology, 2025)
BackgroundResilience—the capacity to adapt effectively to stress and adversity—plays a protective role across psychiatric disorders. Individuals with alcohol use disorder (AUD) often present with lower resilience, potentially influenced by impulsivity, aggression, temperament, and childhood trauma. This study examined how these factors relate to resilience in individuals with AUD.MethodsBetween September 2024 and March 2025, 74 male inpatients with DSM-5-TR–diagnosed AUD were recruited from the University of Health Sciences Bursa Yuksek Ihtisas Training and Research Hospital. Participants completed the Resilience Scale for Adults (RSA), Beck Depression Inventory (BDI), Barratt Impulsiveness Scale-11 (BIS-11), Buss–Perry Aggression Questionnaire (AQ), Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A), and the Childhood Trauma Questionnaire (CTQ). Correlation and regression analyses were conducted.ResultsHigher RSA scores were observed among employed participants and among those without a history of suicide attempts. Depression scores showed weak negative correlations with RSA subscales, particularly social competence and social resources. Impulsivity—especially non-planning impulsivity—showed moderate-to-strong negative associations with resilience and emerged as its strongest predictor. Depressive and irritable temperaments were significant predictors of lower resilience, whereas hyperthymic temperament was weakly positively associated. Childhood emotional abuse and neglect showed a weak but significant negative correlation with resilience—particularly with perception of future—while physical and sexual abuse were not significantly related. Aggression showed no consistent associations with resilience, apart from a weak negative correlation between hostility and perception of future. The final regression model (non-planning impulsivity, depressive and irritable temperaments) explained 35.8% of the variance in resilience.ConclusionIn AUD, resilience is negatively associated with depressive and irritable temperaments and with non-planning impulsivity, and is modestly related to childhood emotional maltreatment. Although shaped by relatively stable traits and early adverse experiences, resilience may be enhanced through psychosocial interventions—particularly those targeting emotion regulation, future orientation, and social support—which could help improve clinical outcomes in AUD.